Perceived barriers to early detection of breast cancer in Wakiso District, Uganda using a socioecological approach - Deborah Ilaboya; Linda Gibson; David Musoke (BMC, 2018)
Abstract Background Early detection of breast cancer is known to improve its prognosis. However, women in most low and middle income countries, including Uganda, do not detect it early hence present at an advanced stage. This study investigated the perceived barriers to early detection of breast cancer in Wakiso district, Uganda using a multilevel approach focused through a socioecological framework. Methods Using qualitative methods, participants were purposively selected to take part in the study. 5 semi-structured interviews were conducted among the community members while two focus groups were conducted amongst women's group and community health workers (CHWs) in Ssisa sub county, Wakiso district. In addition, 7 key informant interviews with health professionals, policy makers and public health researchers were carried out. Results Findings from the study revealed that barriers to early detection of breast cancer are multifaceted and complex, cutting across individual, interpersonal, organizational, community and policy barriers. The major themes that emerged from the study included: knowledge, attitudes, beliefs and practices (KABP); health system and policy constraints; and structural barriers. Prominent barriers associated with KABP were low knowledge, apathy, fear and poor health seeking behaviours. Barriers within the health systems and policy arenas were mostly centred around competing health care burdens within the country, lack of a cancer policy and weak primary health care capacity in Wakiso district. Distance, poverty and limited access to media were identified as the most prominent structural barriers. Conclusion Barriers to early detection of breast cancer are complex and go beyond individual behaviours. These barriers interact across multiple levels of influence such as organizational, community and policy. The findings of this study could provide opportunities for investment in multi-level interventions.